Evaluating perceptions of co-management on small-scale fisheries in the Wild Coast of South Africa - Mthombeni, Vusi Gedla (Rhodes University, Faculty of Commerce, Rhodes Business School)
Shared perceptions by stakeholders can improve the understanding of managing natural resources. This study aimed to evaluate stakeholders' perceptions towards co-management of small-scale fisheries to improve the management of these resources. Eleven participants were purposively sampled from government agencies, non-profit organisations and community representatives from Coffee Bay, Port St Johns, Lusikisiki and Xolobeni on the Wild Coast of South Africa. Predetermined themes derived from the literature were used to develop the interview schedule. Semi-structured, one-on-one interviews were conducted to probe the participants' understanding of the term "co-management" and its objectives, benefits, processes, and outcomes. Data were recorded and transcribed into text, and thematic analysis was used to detect themes that emerged from the data. The results indicated that all participants perceived co-management of Small-scale fisheries as beneficial. Securing access rights through fishing permits was a benefit that was exclusive to the fishers, whereas self-regulation, sharing of information, and mobilising and utilising the strengths of different stakeholders were the benefits noted by all stakeholder participants. Government representatives viewed the involvement of government in the co-management structures of SSF as necessary, whereas the other representatives' views were that government should be excluded. Incorporating the traditional and government regulatory systems was recommended to manage fisheries resources effectively. The benefits of co-management exceeded costs, suggesting that co-management was viable for the Wild Coast.
Keywords: Small-scale fisheries -- South Africa; Fishery co-management; Ecosystem approach; Stakeholder theory; Wild Coast Region